Role of personality traits in the adjustment to diversity - Syed Shameem Ejaz (Universidad de San Buenaventura, 2013)
This article discusses the ‘Scale for the Assessment of Adjustment to Diversity (SAAD)’.The scale measures the individual’s adjustment levels to diverse situations. Adjusting to diverse situations requires extra efforts by individuals, sometimes these efforts fall short and the situation remains invincible. We assumed that there are personality traits (BITPC)1 responsible for success or failure in the adjustment to diverse situations. This five-factor model was evaluated in five diverse (SOGER)2 situations. A CFA, run on the results obtained from 444 (n) individuals, reveals a not converging five-factor model. However, after running CFA – (Confirmatory Factor Analysis) for all possible permutations the BIP – (Broadmindedness, Insight, and Patience), a 3 factor model was found to be the best fit on cutoff points when two top ranked situations were taken into consideration.